Graphene/Al2O3/Si Schottky diode with integrated waveguide on a silicon-on-insulator wafer - Seven, E.; Orhan, E.Öz; Di Bartolomeo, A.; Ertuğrul, M.; Taştekin, N. Avişhan (Springer, 2024)
Waveguide-integrated graphene photodiodes are on-chip optoelectronic devices with promising applications in telecommunications. Here, we present the electrical properties of a heterostructure consisting of multilayer graphene (MLGr) over a Si waveguide covered by an ultrathin Al2O3 layer. The waveguide is fabricated by etching a silicon-on-insulator (SOI) substrate with 220 nm Si and 1.5 μm buried oxide. The 5 nm-thick Al2O3 film is deposited by atomic layer deposition (ALD), while graphene, synthesized on copper by chemical vapor deposition (CVD), is transferred onto the Al2O3/Si rib by a wet transfer method. The MLGr/Al2O3/Si rib forms a Schottky structure with rectifying current–voltage characteristics, which are examined using the thermionic emission theory and Norde’s method. A Schottky barrier height Φ B= 0.79 eV , an ideality factor n = 26, and a series resistance R S= 11.6 M Ω are obtained. The device is promising for operation at the optical fiber communication wavelength of 1550 nm.